Age-related peridural hyperemia in craniosynostotic rabbits - Foley, Lesley M. (2009)
OBJECTIVE: Craniosynostosis is the premature fusion of the calvarial sutures and is associated with aesthetic impairment and secondary damage to brain growth. Associated neurological injuries can result from increased intracranial pressure (ICP) and abnormal cerebral blood flow (CBF). Arterial spin-labeling (ASL) MRI was used to assess regional CBF in developing rabbits with early-onset coronal suture synostosis (EOCS) and age-matched wild-type controls (WT). METHODS: Rabbits were subjected to ASL MRI at or near 10, 25, or 42 days of age. Differences in regional CBF were assessed using one-way ANOVA. CONCLUSION: CBF was similar in WT and EOCS rabbits with the exception of the peridural surfaces in EOCS rabbits at 25 days of age. A twofold increase in peridural CBF at 25 days of age coincides with a transient increase in ICP. By 42 days of age, CBF in peridural surfaces had decreased.